Deslocamento compulsório em Breu Branco: experiência da perda e perda da experiência na dinâmica de habitar - MERCÊS, Jorge Augusto Santos das (Universidade Federal do Pará, 2023)
This research deals with the memory of people compulsorily displaced since 1984 by the implementation of the Tucuruí Hydroelectric Power Plant (UHE-Tucuruí). From a phenomenological approach to the problem, the thesis proposes to understand and describe the flows of memory of an event of intense violence in what is lost, sometimes in the form of concealment of meaning as a political strategy; sometimes as an interdiction of the signifier in the chain of meaning, aiming at the contribution of this dynamic to the conformation of affections related to dwelling. For this purpose, field research with an ethnographic profile was carried out in intermittent months between 2016, 2017 and 2018 and in 2022. During the periods of field work, participant observation was carried out, with immersion in the daily life of the interlocutors of this research, consultation with personal files composed , above all, for photos; as well as carrying out semi-structured and non-structured interviews with compulsorily displaced people in the municipality of Breu Branco during the first phase of the UHE-Tucuruí works, which took place between the years 1970 and 1980. The filling of the reservoir of this hydroelectric plant caused the submersion of fourteen villages, among them, Breu Velho (object of this research). Bearing in mind that this research was carried out in parts during the new coronavirus pandemic (2020- 2022), field research was conditioned by the severity of the problem at each moment, bearing in mind that my interlocutors are elderly people and, therefore, , were part of the risk group in the ongoing pandemic until that moment. The data demonstrate how the phenomenon of intense violence implied in compulsory displacement operates through the dynamics of inheritance – the latencies and silences of the social process that keeps memory in the field of dispute. In this way, on the one hand, the rationalized silences in the social process of dispute over memory find a way of enunciation in alternative environments to the rules that the dominant rationality in disciplinary institutions imposes on what it considers reasonable. On the other hand, as an ontological experience of trauma through the interdiction of the signifier, the silences, the voids of meaning, can be glimpsed either in the symptoms that the trauma manifests when introducing the law of repetition of symptomatic acts present in the structure of action of the subjects, or by the outline that the meanings make of this experience, coloring the narratives about the experience of loss with melancholic affection. It is emphasized that, in the case in question, the reparation processes operate in a region of the Being different from that in which the trauma is inscribed; since the objectification of the loss is conducted on ontic soil, while the trauma is manifested in an ontological region.